Increasing Knowledge Through Health Education About 3m To Prevent DHF (Dengue Haemoragic Fever) - Amanda Indrika, Elke; Sulaiha, Siti; Soleha, Umdatus; Faizah, Imamatul; Kamariyah, Nurul (Sean Institute, 2023)
Dengue fever is a disease transmitted by mosquitoes and occurs in tropical and subtropical regions worldwide. Mild dengue fever causes high fever and flu-like symptoms. Prevention of dengue fever can be done by providing knowledge about its prevention, namely through the 3M approach. This community service implementation aims to educate about the prevention of dengue fever. The method used is by providing health education through pre-tests and post-tests to families and patients. This activity was carried out during March 2023 in Room Azzahra 1, Jemursari Hospital, Surabaya. The research results show that the activity has achieved the intended objectives, which include participants actively participating in the activity, a significant difference between pre-tests and post-tests, and participants providing feedback during the counseling session. The conclusion of this research is that providing education on the 3M approach effectively enhances participants' knowledge in the prevention of dengue fever.